Current anti-doping crisis: The limits of medical evidence employing inductive statistical inference - Simon, P.; Dettweiler, U. (Sports Medicine, 2019)
The anti-doping system is supposed to level the playing field and protect clean athletes. Doping scandals of the past two decades have seriously questioned the effectiveness of the worldwide anti-doping program, and criminal investigations associated with those scandals have created evidence for its partial ineffectiveness. However, legal action often succeeded because of activities from within the anti-doping community, such that the looming ineffectiveness could still be interpreted as a sign of an isolated shortcoming of the drug-testing program, while the overall "system of anti-doping" was still effective and working. In other words, from within the anti-doping system, we may not be able to assess its own effectiveness.